2013
DOI: 10.5817/cp2013-1-8
|View full text |Cite
|
Sign up to set email alerts
|

Young people’s creative online practices in the context of school community

Abstract: This article concentrates on young people's creative online practices, such as making videos, writing lifestyle blogs, and engaging in online role-playing games. It also looks at their relations to different audiences, privacy, and the school community as a central social environment in young people's everyday life.The research was conducted as an ethnographic study in one public secondary school in Finland during the academic year 2009-2010. The ethnography is preceded by a quantitative survey on media use am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
6
0
2
Order By: Relevance
“…Gibbons (2013) suggested that presenting one's identity in networked media is challenging for young people. Adolescents who are conscious of their developing web image (Kupiainen, 2013a) may become more reluctant, afraid of receiving nasty comments, being bullied, and losing their credibility among their peers. Furthermore, they might consider online publishing as a context that they want to leave as an option for themselves, probably due to a perceived feeling of control or power relations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Gibbons (2013) suggested that presenting one's identity in networked media is challenging for young people. Adolescents who are conscious of their developing web image (Kupiainen, 2013a) may become more reluctant, afraid of receiving nasty comments, being bullied, and losing their credibility among their peers. Furthermore, they might consider online publishing as a context that they want to leave as an option for themselves, probably due to a perceived feeling of control or power relations.…”
Section: Discussionmentioning
confidence: 99%
“…As the term media includes the new media with interactive and networking 5 characteristics enabled by digital technologies (Ylä-Kotola & Arai, 2000), media education aims at enhancing media or digital literacies. Although media (or digital) literacy involves the production of digital works (Buckingham, 2006), it has not traditionally addressed privacy management in the networked public (Kupiainen, 2013a). Still, an aspect emphasizing online safety has been included in digital literacy (Buckingham, 2006): basic technical skills are not enough, but it is crucial to learn how to protect oneself against harmful content.…”
Section: Integrating Publicity Media Education and New Literacies Pmentioning
confidence: 99%
See 2 more Smart Citations
“…Käytän artikkelissa empiiristä aineistoa tutkimuksestani vuosilta 2009-2010 Nuoret, lukutaidot ja muuttuva mediaympäristö (Kupiainen 2013b) valaisemaan mainittujen mediakäytäntöjen luonnetta. Etnografinen tutkimus on toteutettu länsisuomalaisessa yläkoulussa, mutta tutkimukseen kuului myös nuorten mediakäytäntöjen ja nettijulkaisemisen seuraaminen.…”
Section: Nuorten Luovat Mediakäytännöt Kaupunkitilan Heterotopioinaunclassified